The effect of the treatment cards and scale strategies on written expression among fifth-grade primary school students (Journal of the College of Basic Education, 2023)
This study aims to identify “the effect of the treatment cards and scale strategies on written expression among fifth-grade primary school students.” The researcher followed the experimental research approach and chose an experimental design with partial control for the three research groups appropriate to the circumstances of the current research. The researcher randomly chose (Al-Nubalaa) School for Boys, affiliated with the Holy Karbala Education Directorate, to represent the research sample. The school included (4) classes for the first intermediate grade, and by random drawing method, the researcher chose Class (C) to represent the first experimental group of (38) students, and Class ( A) to represent the second experimental group, which numbered (36) students, and (B) to represent the control group, which numbered (37) students. The researcher rewarded the research groups in variables (the chronological age of the students calculated in months, the academic achievement of the fathers and mothers, the scores of the Arabic language subject in the mid-year test for the fifth grade of primary school for the academic year 2021/2022, the Raven intelligence test). The researcher identified the scientific material included in the experiment with eight literary topics from the reading book for the fifth grade of primary school. Then she formulated behavioral objectives in accordance with the prescribed educational material, reaching (148) cognitive behavioral objectives within Bloom’s classification for the first three levels of the classification. Then she prepared study plans for groups. During the three studies, the experiment lasted a full semester of the academic year (2021-2022 AD), which is the first semester.The researcher used the following statistical methods appropriate for her research procedures (Smirnov test for normal distribution, Levene's test for homogeneity, one-way analysis of variance, chi-square, Pearson's correlation coefficient, difficulty coefficient, discriminatory power coefficient, effectiveness of false alternatives, Al-Facronbach equation, Schiff's method, and eta for effect size. ).The researcher also concluded some results, including:1- The current research contributed to finding a solution to the problem of the low level of reading comprehension and written expression among fifth-grade primary school students by presenting the material in a different and distinctive way.2- The two strategies (treatment cards and scales) contributed to raising the level of reading comprehension and written expression among students in the two experimental groups, compared to those in the control group. The researcher also made a number of recommendations, including:1- The need to support teachers in primary schools and encourage them to use modern strategies in teaching.2- The necessity of directing and encouraging the use of (processing cards and scales) in teaching reading material for the fifth grade of primary school. The researcher proposed a number of proposals, including:1- A study similar to the current research, provided that it is different in its dependent variables, such as (achievement, acquisition of rhetorical concepts, and critical, deductive, or creative thinking).2- Conducting a study similar to the current research on females. The results showed that the two experimental groups outperformed the control group in the reading comprehension and expressive performance test.